Energy Saving Potential Analysis of Waste HeatRecovery for Electric Vehicles under Low Temperature Operating Conditions - WANG Tianying (Zhileng xuebao)
Efficiency of their thermal management system directlyaffects the energy consumption and range of the vehicle with the widepopularity of electric vehicles. The new integrated thermal management heatpump system and control strategy for configuration are proposed in this paper,and deeply analyzes its performance in low-temperature environments for wasteheat recovery systems. By designing experiments with different powers andcomparing the coefficient of performance (COP) of refrigeration, it wasconfirmed that the strategy of controlling waste heat recovery conditionsthrough a six-way valve can significantly reduce the energy consumption of thethermal management system. In addition, this article also conducted realvehicle tests on the system, and at ambient temperatures of -7 °C and -18°C, the energy consumption ofthe first hour equipped with a waste heat recovery system (RWH) was reduced by24% and 35%, respectively, demonstrating its significant effect on improvingenergy efficiency in extreme low temperature environments. In verifying theenergy-saving potential of the waste heat recovery system in practicalapplications, the range of electric vehicles increased by 22.95% in urbanconditions and 37.29% in high-speed conditions, providing theoretical and experimentalbasis for the design and optimization of thermal management systems.